2020
DOI: 10.17162/au.v11i1.559
|View full text |Cite
|
Sign up to set email alerts
|

Conducta y actitud ambiental responsable en estudiantes universitarios en Lima, Perú

Abstract: La actitud hacia el ambiente constituye un indicador de la conducta ambientalista y se manifiesta en la acción y las regulaciones proambientales. El objetivo de este estudio fue conocer la relación entre la conducta y la actitud ambiental responsable en estudiantes universitarios en Lima, Perú. El enfoque fue cuantitativo, con diseño descriptivo-correlacional y la muestra estuvo conformada por 287 estudiantes hombres y mujeres de diversas carreras. Los instrumentos utilizados fueron dos escalas que miden la ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
2
1
0
Order By: Relevance
“…According to some studies, having a connection with nature might generate a greater environmental concern ( Schultz, 2000 ) and a commitment to protect the environment ( Wu and Zhu, 2021 ). However, in line with studies that found a gap between pro-environmental attitudes and pro-environmental behavior ( Newsome and Alavosius, 2011 ; Páramo, 2017 ; Olivera et al, 2020 ), our results suggest that although the positive perceptions of the sea might encourage intentions of engaging in pro-environmental behaviors, in the case of most participants these intentions do not translate into pro-environmental behaviors, especially if it involves greater effort. Participants acknowledge that even if they feel connected to the sea, they do not engage in collective actions aimed at reducing marine plastic pollution in a systematic way.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to some studies, having a connection with nature might generate a greater environmental concern ( Schultz, 2000 ) and a commitment to protect the environment ( Wu and Zhu, 2021 ). However, in line with studies that found a gap between pro-environmental attitudes and pro-environmental behavior ( Newsome and Alavosius, 2011 ; Páramo, 2017 ; Olivera et al, 2020 ), our results suggest that although the positive perceptions of the sea might encourage intentions of engaging in pro-environmental behaviors, in the case of most participants these intentions do not translate into pro-environmental behaviors, especially if it involves greater effort. Participants acknowledge that even if they feel connected to the sea, they do not engage in collective actions aimed at reducing marine plastic pollution in a systematic way.…”
Section: Discussionsupporting
confidence: 88%
“…Pro-environmental behavior comprises deliberate and effective actions aimed at protecting the environment ( Páramo, 2017 ; Rivera-Torres and Garcés-Ayerbe, 2018 ). However, despite the wide acceptance of the research of environmental attitudes, several studies report inconsistent results regarding a statistically significant relationship between attitude and pro-environmental behavior ( Newsome and Alavosius, 2011 ; Páramo, 2017 ; Olivera et al, 2020 ). This might be linked to the weighting of values, such as competition and individualism, within society that influences selfish attitudes ( Corral et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same sense, the research by Handayani et al (2021) indicates that individuals with a high level of attitude toward the environment are more likely to manifest positive pro-environmental behaviors. Michalos et al (2009) obtained similar results with a sample of Manitoban adults and youth, and Olivera et al (2020) also pointed out that the environmental attitude of university students is an indicator of pro-environmental behavior, regardless of gender and the study area.…”
Section: Resultssupporting
confidence: 54%
“…The previously described finding is consistent with that reported by Mamani et al (2020), who determined that Peruvian students in regular basic education had behaviors of indifference towards the environment and its conservation, which translated into a lack of interest in promoting the preservation of natural and environmental resources, as well as promoting sustainable use of them and the reduction of environmental pollution. In the same way, also in Peru, they reported that pro-environmental behavior in students was located at the medium level, which indicated that on certain occasions they carried out actions to favor the care and conservation of the environment (Olivera et al 2021).…”
Section: Discussionmentioning
confidence: 73%